Cross-National Variation in the Relationship between Welfare Generosity and Single Mother Employment - Thomas Biegert; David Brady; Lena Hipp (The ANNALS of the American Academy of Political and Social Science, 2022)
Reform of the U.S. welfare system in 1996 spurred claims that cuts to welfare programs effectively incentivized single mothers to find employment. It is difficult to assess the veracity of those claims, however, absent evidence of how the relationship between welfare benefits and single mother employment generalizes across countries. This study combines data from the European Union Labour Force Survey and the U.S. Current Population Survey (1992-2015) into one of the largest samples of single mothers ever, testing the relationships between welfare generosity and single mothers' employment and work hours. We find no consistent evidence of a negative relationship between welfare generosity and single mother employment outcomes. Rather, we find tremendous cross-national heterogeneity, which does not clearly correspond to well-known institutional variations. Our findings demonstrate the limitations of single country studies and the pervasive, salient interactions between institutional contexts and social policies.
doi:10.25384/SAGE.21657196.v1
Keywords: 330; single mothers; employment; welfare state benefits; cross-national; heterogeneity